Ellagic acid attenuates beryllium sulphate-induced oxidative stress and histopathological alterations of spleen in rats - Yuandi Lei; Tianyi Jiang; Liqin He; Yanping Liu; Zhanbing Sun; Weihua Deng; Lian Huang; Zhaohui Zhang (Taylor & Francis Group, 2022)
Context Ellagic acid (EA) is a phenolic constituent in certain fruits and has largely been recognized for its role as an antioxidant compound.Objective To evaluate the effect of EA on beryllium sulphate-induced splenic toxicity in rats.Materials and methods Male Sprague-Dawley rats were divided into four groups. The first group was used as control. Group 2 was exposed to BeSO4 (12 mg/kg, b.w.). Groups 3 and 4 were treated with EA (100 and 300 mg/kg, b.w.) daily for 6 weeks after exposing to BeSO4 (12 mg/kg, b.w.). Various biochemical and molecular biomarkers were assessed in blood and spleen.Results BeSO4-intoxicated rats showed significant higher WBC (6.74 ± 0.20 × 109/L vs. 11.02 ± 1.31 × 109/L, p < 0.05), Neu (1.14 ± 0.11 × 109/L vs. 2.45 ± 0.42 × 109/L, p < 0.05), Lym (3.80 ± 0.83 × 109/L vs. 9.64 ± 1.99 × 109/L, p < 0.05), and PLT (868.4 ± 43.2 × 109/L vs. 1408 ± 77.57 × 109/L, p < 0.05) than normal control animals. Moreover, an increase in MDA with depletion of GSH and SOD activity (all p < 0.05) occurred in the spleen of rats treated with BeSO4. Furthermore, BeSO4-treated rats displayed significantly higher levels of apoptotic markers (Bax, Caspase-3, PARP) (all p < 0.05). EA administration resulted in a significant reversal of hematological and apoptotic markers in beryllium sulphate-intoxicated rats.Discussion and conclusions Our results suggest EA treatment exerts a significant protective effect on BeSO4-induced splenic toxicity in rats.